Mitochondrial DNA copy number, damage, repair and degradation in depressive disorder. (7th February 2020) - Czarny, Piotr; Wigner, Paulina; Strycharz, Justyna; Swiderska, Ewa; Synowiec, Ewelina; Szatkowska, Magdalena; Sliwinska, Agnieszka; Talarowska, Monika; Szemraj, Janusz; Su, Kuan-Pin; Maes, Michael; Sliwinski, Tomasz; et al.
Abstract: Objectives: We aimed to explore mitochondrial DNA (mtDNA) copy number, damage, repair and degradation in peripheral blood mononuclear cells (PBMCs) of patients with depression and to compare the results with healthy subjects. Methods: Total genomic DNA was isolated from PBMCs of 25 depressed and 60 healthy subjects before, immediately after, and 3 h after the exposure to H2 O2 . Evaluation of mtDNA copy number was performed using real-time PCR and 2-ΔCt methods. Semi-long run real-time PCR was used to estimate the number of mtDNA lesions. Results: Baseline mtDNA copy number did not differ in cells of healthy and depressed subjects; however, it was negatively correlated with the severity of the episode. After a 10-min challenge with hydrogen peroxide (H2 O2 ), depressed patients' PBMCs exhibited slower changes of the copy number, indicating a lower efficiency of mtDNA degradation compared to controls. Moreover, a significantly higher number of mtDNA lesions was found in depressed patients at the baseline as well as at other experimental time points. mtDNA lesions were also elevated in depressed patient cells immediately after H2 O2 exposure. Induction of oxidative stress had no significant influence on the cells of controls. Conclusions: We are the first to show that impairment in repair and degradation of mtDNA may be involved in the pathophysiology of depression.